Isti'mal Harf al faa'u fi al Asaaliib al 'Arabiyah - Wahyuddin, Wahyuddin (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2020)
Among the topics of grammar is the use of the harf al-fâ in the styles of the Arabic language. This writing is intended to highlight the important issues related to this letter. Whether it is its types, how it is used in linguistic methods, or its meanings. The use of the harf al-fâ in Arabic language styles varies. It comes in several signs: 1. Harf al-‘atf. 2. Harf isti’naf. 3. Harf  râbit jawâb al-syart. 4. Harf sababiy. 5. Harf ta’lil. 6. Harf zâidah 7. Fi’il amar. Therefore, it is better for us to master it well, because it has an important and even more important role in understanding the meanings of the Noble Qur’an, hadith and other Arabic books.